Incidence of maternal desaturation among patients undergoing elective caesaraen section under regional anaesthesia - Farhana K,; Lee, Choon Yee; Thohiroh AR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
This was a prospective observational study to identify the incidence and possible risk factors for maternal desaturation following neuraxial blockade for elective caesarean section (CS). Patients with body mass index (BMI) ≥ 30 kg/m2 at the first antenatal consultation were identified and classified into the obese group. Neuraxial blockade in the form of subarachnoid block (SAB) or combined spinal-epidural (CSE) was performed. Mean arterial pressure (MAP) and oxygen saturation (SpO2) were recorded at baseline and at 5-minute intervals following neuraxial blockade. Desaturation, defined as SpO2 < 94% for more than 30 seconds without artifacts, was managed with oxygen therapy and other appropriate measures. Newborn Apgar score and umbilical cord blood gases were analysed. Among a total of 254 recruited patients, 69 (27.2%) were obese and were associated with significantly higher age, parity, previous CS and pre-existing diabetes mellitus. The incidence of oxygen desaturation was 1.2%, involving three patients in the non obese group. These desaturation episodes were short-lived and associated with intraoperative hypotension. Six patients, two of whom in the obese group, received rescue oxygen therapy following intraoperative events such as deteriorating SpO2 or hypotension. The mean MAP was significantly lower at baseline and at 5 minutes post neuraxial blockade in the non obese group, which could account for the occurrence of desaturation in this group only. There were no significant inter-group differences in terms of neonatal outcome, umbilical cord blood gases and changes in mean SpO2 post neuraxial blockade. In conclusion, the current practice of not routinely giving supplementary oxygen to patient during elective CS at our institution is deemed to be safe, provided continuous SpO2 monitoring is available throughout the surgery. Further randomised clinical trials are indicated to investigate the impact of maternal obesity and of labouring patients presenting for urgent or emergency CS on intraoperative oxygen desaturation.